Effect of Workwear Fabric Fluorocarbon Coating on Changes in Tensile Properties of Sewing Threads - Muralidhar B.A. (Tekstilec, 2022)
This paper presents the findings of changes in the tensile behaviour of sewing threads in two-seam configuration on three different workwear fabrics, i.e. drill, duck and rip-stop structures, before and after the coating. For this research, commercially available workwear fabrics were obtained from the domestic industry and the sewing was carried out using a 40 tex core-spun polyester sewing thread. High-speed heavy-duty lockstitch sewing machines were used to construct both the superimposed (SSa) and lapped seams (LSd). The strength of sewing threads sewn in the two-seam configuration were carefully unravelled and compared with the unsewn sewing thread (UST). The effect of coating on the changes in tenacity, breaking elongation and initial modulus of the needle thread was reported. It was found that there was a significant effect of weave structure on the tenacity of the sewing thread.